Case commentary Sri Inai (Pulau Pinang) Sdn Bhd v Yong Yit Swee : the duty of care owed by a landlord to the lawful visitors of a tenant / Dr. Irwin Uj Ooi - Irwin, Uj Ooi (Faculty of Administratron and Law, 2004)
The case of Sri Inai (Pulau Pinang) Sdn Bhd v Yong Yit Swee & Ors[ would have gone largely unnoticed as a routine appeal on the duties owed by a landlord to lawful visitors of his/her tenant if one had not taken note of one of the submissions put forward for consideration before the High Court. The fact that this submission was actually made by counsel was due either to an ignorance of one of the fundamentals of the law on negligence, or a very audacious attempt at changing the law that has stood since Donoghue v Stevenson.1 Ever since the groundbreaking efforts of Lord Atkin and the majority of the House of Lords3 more than 70 years ago, there was no requirement in negligence that a claimant had to have a pre-existing contractual relationship with the defendant to establish a duty of care. The High Court's application of an even older English authority opened up the possibility of a revival of the pre-Donoghue common law position in Malaysian law. The Court of Appeal consisting of Gopal Sri Ram JCA, Abdul Kadir Sulaiman JCA and Alauddin JCA in Sri Inai (Pulau Pinang) Sdn Bhd was therefore presented with an opportunity to either reaffirm the well-established rule in Donoghue or regressing to the dark ages of the common law.